Effect of ambient temperature and hydrated status on heart rate recovery after a standardized step test - Lee, H. H.; Liao, Y. H.; Tsai, T. J.; Wang, T. R.; Tseng, C. H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of the study was to determine whether differences in ambient temperature and water drinking status could cause variation in the result of a government-made standardized step test. The results show that ambient temperature of the testing environment and dehydration condition of the testing subjects appear to be confounding factors for the result of the 3-min step test as an indicator for cardiopulmonary fitness.